Marital Rape in a Comparative Perspective of Indonesian Criminal Law and Islamic Criminal Law - Laely Wulandari; Lalu Saipudin (Faculty of Law, University of Mataram, 2021)
The aim of this research is to know how the regulation of marital rape in Indonesian Criminal Law and Islamic Law. Marital rape or also known as rape in marriage still belong to such a debatable and taboo topic, but in fact it has happened a lot in society. In Indonesian Criminal Law, marital rape is not regulated in the Criminal Code. The Law on the Elimination of Domestic Violence regulates this as a complaint offense by calling the crime of sexual violence. In Islamic Law, marital rape is regulated in a good way by terms of husband and wife intercourse, among others in Surah An-Nisa Verse 19 which prohibits having to do with coercion. Refers to these results of the comparison, similarities are found in both Indonesian Criminal Law and Islamic Criminal Law that said marital rape is prohibited. The differentials in the form of complaint offense between these laws. Islamic Criminal Law does not explain clearly about the complaints offense as known on Indonesian Criminal Law. Yet this law comprehensibly prohibiting the marital rape itself. For the further regulations of criminal law policies, it should take the principles of discrimination into account and the good boundaries regarding marital rapes, criminal liability, criminal threats and formal criminal arrangements either.